ANALISIS ALTMAN UNTUK MEMPREDIKSI KEBERLANGSUNGAN USAHA LEMBAGA KEUANGAN MIKRO SYARIAH DI KABUPATEN TANAH DATAR - YENTI, ELFINA (Faculty of Shariah of State Institute for Islamic Studies Batusangkar, Indonesia, 2016)
This research was conducted to predict the business continuity (going concern) microfinance institutions sharia in tahah datar using the Altman Z-Score. The purpose of this research was to analyze the performance and predict the sustainability of microfinance institutions sharia in tanah datar. Because of the presence of islamic micro finance institutions in tanah datar help people who need additional capital, because people have limited access to other financial institutions, especially banks. The result of this research are expected to be considered by the management to increase or improve the state of the company in the future. For the goverment is expected to have implications for the measures taken, as the goverment took responcibility for the empowermenr of micro, small and medium enterprices as referred to in the Act No. 20 of 2008.